VALIDITY OF CRYPTOCURRENCY AS DOWRY IN MARRIAGE IN INDONESIA PERSPECTIVE OF ISLAMIC LAW - Farhan, Muhammad Faiz; Saiban, Kasuwi (Hukum Islam, 2024)
This study examines the validity of cryptocurrency as a dowry in marriage in Indonesia from the perspectives of Islamic law and positive law. Technological advancements have driven the use of crypto assets as dowries, sparking debates regarding their legitimacy and mechanisms. This research aims to analyze these issues using a normative approach with contemporary ijtihad methods (intiqa’i and insya’i) and a statute approach. The findings reveal that, in general, the Indonesian Ulema Council (MUI) prohibits the use of cryptocurrency as a medium of exchange or commodity, except when it fulfills the requirements of sil’ah. In the context of national law, crypto assets can be used as dowries if agreed upon by both parties. The transfer mechanism requires a grant process before a notary to ensure legal validity. This study has implications for the development of regulations and legal understanding regarding the use of modern technology in religious traditions.Key words: Cryptocurrency, Dowry, Islamic Law, Positive Law, Technology.